The pathophysiology and complications of Fontan circulation - Mazza, Giuseppe Antonio; Gribaudo, Elena; Agnoletti, Gabriella (Acta Biomedica Atenei Parmensis, 2021)
The Fontan operation has been the final palliation for patients born with congenital heart defects with a functional single ventricle for more than 4 decades. The “normal” Fontan physiology is characterized by the loss of the sub-pulmonary ventricle with consequent elevated pressure in the caval system, non-pulsatile blood flow in the pulmonary circulation and at least mild reduction of the systemic output. When successful, this procedure is associated with a range of benefits including improved arterial saturation and abolishment of chronic volume overload, allowing a fairly normal life to the majority of patients through early adulthood. As we enter the 5th decade of caring for patients palliated with the Fontan procedure, it is evident that adult survivors face significant morbidity due to multiorgan dysfunction, early mortality and need for heart transplantation. Several late complications may occur: ventricular dysfunction, arrhythmia, cyanosis, exercise intolerance, elevated pulmonary vascular resistance, protein-losing enteropathy, plastic bronchitis, hepatic and renal complications. The mechanism of late Fontan failure is multifactorial and not completely understood, it depends on interactions between the ventricle, the pulmonary vascular bed, the venous and lymphatic compartments.Conclusions: the aim of this review is to describe the pathophysiology of Fontan circulation and the clinical and hemodynamic characteristics of early and late failing Fontan survivors, their association with morbidity and mortality, and the strategies for their management.